Smart traffic sign games: innovation technology based on interactive surface and augmented reality for early childhood / Anton Agus Setiawan ... [et al.] - Setiawan, Anton Agus; Andani, Rani Wahyu; Rokhim, Deni Ainur; Afandi, Riza Aulia; Putra, Wahyu Pratama (Universiti Teknologi MARA, Kedah, 2019)
Indonesia has placed the second position in ASEAN as the country with the highest accident rate based on data Head of the Police Traffic Corps of the Republic of Indonesia in 2017. That accidents due to the low level of ethics and orderly culture related to road users. Smart Traffic Sign Games is interactive multimedia developed to build the character of early childhood so that they can drive safely. It offers innovation by utilizing interactive surface technology combined with augmented reality technology so it develops learning that invites students to play while learning directly how traffic works. The concepts are (1) transforms classroom floor surfaces into interactive surfaces with the help of WII Remote and infrared sensors mounted on toy cars, (2) virtual traffic environment projected through the projector to the surface floor, (3) when the toy car is run by students and approaches one of the traffic signs, an audio will appear explaining the functioning of the traffic signs and (4) if a toy car violates the rules of traffic signs, there will be audio describing the warnings and prohibitions. It has been tested and gone through the repair stage. Then it has given results to basic education to traffic and has a product feasibility value on top of 85%. In addition, it has been published in proceedings and published in international conferences as a contribution to the world of education and has the potential to be commercialized because of its innovation, easily available and affordable prices.